Keberagamaan dan Dakwah Tionghoa Muslim - Abidin, Yusuf Zainal (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
Research on the religious activities and daâ€™wah of Chinese Muslims in Indonesia are still very minimal, even though this ethnic group also contributes to the spread of Islam in Indonesia. This study describes the diversity and propaganda of Muslim Chinese in the city of Bandung. With the case study method, we find out how the religious experience and da'wah of Muslim Chinese as a form of thought, deed and congregation. The results of the study revealed that diversity and da'wah among Muslim Chinese is a social act as part of religious experience in the form of (1) thought that religious diversity is not only limited to facts social that the Chinese ethnic are Muslims, but also felt and lived in the form of social interaction. (2) rites, da'wah activities for the ethnic Chinese need an initial study of their ancestral culture and (3) congregation in the form of support from external Chinese Muslims and the spirit of some of them to unite in the form of activities in the Laotze 2 mosque and in the Al-Imtizaj mosque Bandung. Kajian tentang keberagamaan dan dakwah Tionghoa Muslim di Indonesia masih sangat minim, padahal etnis ini juga turut memberikan kontribusi bagi penyebaran Islam di Indonesia. Penelitian ini menggambarkan keberagamaan dan dakwah Tionghoa muslim di Kota Bandung. Dengan metode studi kasus dicari bagaimana pengalaman keagamaanÂ dan dakwah tionghoa muslim sebagai bentuk pemikiran, perbuatan dan persekutuan Hasil penelitian mengungkapkan bahwa keberagaman dan dakwah di kalangan Tionghoa Muslim merupakan tindakan sosial sebagai bagian dari pengalaman keagamaan berbentuk (1) pemikiran yaitu keberagamaan tidakÂ hanya terbatas pada fakta sosial bahwa etnisÂ Tionghoa beragama Islam, tetapi juga dirasakan dan dihayati dalam bentuk interaksi sosial. (2) ritus, kegiatan dakwah bagi etnis Tionghoa memerlukan kajian awal tentang budaya leluhur mereka dan (3) persekutuan berupa dukungan dari pihak eksternal Tionghoa Muslim dan semangat sebagian dari mereka untuk bersatu yaitu dalam bentuk aktivitas di masjid Laotze 2 maupun di masjid Al-Imtizaj Bandung.